STRATEGI PENGEMBANGAN SERULINGMAS INTERACTIVE ZOO OLEH PERUSAHAAN UMUM DAERAH TAMAN REKREASI MARGASATWA SERULINGMAS BANJARNEGARA - Putri, Civanda Adi; Herawati, Nunik Retno; Erowati, Dewi - (Journal of Politic and Government Studies, 2024)
The existence of Regional Regulation Number 5 of 2017 concerning the Establishment of the Serulingmas Wildlife Recreational Park Regional Public Company means that the Serulingmas Interactive Zoo tourist attraction changed its ownership from the Tourism and Culture Department to the Regional Public Company. This change in management was motivated by a policy from the Ministry of Forestry and Environment which states that zoos are included in conservation tourism whose management must be based on independence so that management is not bound by regulations which often make development difficult. Through these problems, the privatization of Perumda TRM Serulingmas was carried out in order to increase operational efficiency, improve service quality, and reduce the burden on the regional government budget. This research aims to examine the strategy for developing the Serulingmas Interactive Zoo tourist attraction by Perumda Serulingmas Wildlife Recreation Park using strategic management and privatization theories. The aim of this research is to analyze the development strategy of Perumda TRM Serulingmas towards the Serulingmas Interactive Zoo tourist attraction. The research method used is a descriptive qualitative method. The research results show that the privatization of Perumda TRMS Serulingmas in the development of the Serulingmas Interacive Zoo has had a positive impact as seen from the increase in capacity and quality of facility functions and services, tourism image and attractions, partnerships, tourism cooperation, HR capacity and capability as well as promotions carried out through digital marketing in various social media. However, there are several things that are not appropriate and need to be used as evaluation material, namely that income has not been achieved due to the lack of support in terms of capital and investment from the local government to help with the Serulingmas Interactive Zoo development plan